2008
DOI: 10.3899/jrheum.080192
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Osteoprotegerin and Soluble RANK Ligand in Systemic Sclerosis

Abstract: Higher sRANKL levels and sRANKL/OPG ratio in patients with SSc are likely to be a consequence of altered bone microenvironment. We show a dissociation between the well established marker of endothelial activation/injury, sVCAM, and the alleged marker of vascular damage, OPG, in patients with SSc. Further studies are needed to better ascertain the relationships of the RANKL/RANK/OPG system with the progression of macro- and microvascular damage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 40 publications
1
24
0
2
Order By: Relevance
“…Their remarkable findings confirm the results of our work, to our knowledge the first controlled study to demonstrate an increased prevalence of hypovitaminosis D in SSc 3 . The renewed interest in vitamin D in autoimmune diseases gives us the opportunity to show previously unpublished data and make some observations about this issue.…”
Section: Hypovitaminosis D In Systemic Sclerosissupporting
confidence: 91%
See 1 more Smart Citation
“…Their remarkable findings confirm the results of our work, to our knowledge the first controlled study to demonstrate an increased prevalence of hypovitaminosis D in SSc 3 . The renewed interest in vitamin D in autoimmune diseases gives us the opportunity to show previously unpublished data and make some observations about this issue.…”
Section: Hypovitaminosis D In Systemic Sclerosissupporting
confidence: 91%
“…Our study comprised 60 patients and 60 matched controls 3 . 25OHD levels were lower in patients than in controls [median 23 ng/ml (range 3-92) and 39 ng/ml (14-138), respectively; p < 0.001] even after matching for season of sampling.…”
Section: Hypovitaminosis D In Systemic Sclerosismentioning
confidence: 99%
“…The patients in that study included both fertile and postmenopausal women. Higher sRANKL levels and sRANKL/OPG ratio were found in patients with SSc and Turk et al . pointed out that TNF‐α has a strong association with the osteoclastogenic mediator RNKL, and an inverse association with BMD, in patients with Crohn's disease (a kind of inflammatory bowel disease caused by abnormal autoimmune status) .…”
Section: Discussionmentioning
confidence: 93%
“…One study that included 60 SSc patients showed that circulating levels of osteoprotegerin, but not RANKL, were higher in those with calcinosis. The authors suggested that this probably represented an inadequate compensatory response of osteoprotegerin as an inhibitor of calcification [25]. Two case reports showed successful use of bisphosphonates for the treatment of calcinosis in SSc patients suggesting that impaired bone metabolism may play a role in the pathogenesis of calcinosis [26,27].…”
Section: Discussionmentioning
confidence: 99%